Acute Vertigo After COVID-19 Vaccination: Case Series and Literature Review - Di Mauro, Paola; La Mantia, Ignazio; Cocuzza, Salvatore; Sciancalepore, Pasqua Irene; Rasà, Deborak; Maniaci, Antonino; Ferlito, Salvatore; Tundo, Isabella; Anzivino, Roberta (Frontiers in Medicine, 2022)
Objective: The aim of this study was to present some cases of acute vertigo potentially related to the coronavirus disease 2019 (COVID-19) vaccine and review the available literature about cochleovestibular dysfunction after the COVID-19 vaccination. Methods: In the period from May to July 2021, we evaluated 33 patients (mean age 54.3 ± 14.1) with “acute vertigo” post COVID-19 vaccination. A detailed medical history was taken on comorbidities, types of vaccines received, and symptoms associated. All patients underwent otoneurological evaluation, such as head impulse test, nystagmus evaluation, test of skew (HINTS) examination. Head shaking test-induced nystagmus, hyperventilation-induced nystagmus, and parossistic positional nystagmus were studied to search for vestibular impairment. Results: Symptoms included 16 patients (48.5%) with objective vertigo, 14 patients (42.4%) with subjective vertigo, and 3 patients (9.1%) with dizziness. Of the associated ear, nose, and throat (ENT) symptoms, the most expressed was tinnitus (18.2%). Bedside examination showed absent nystagmus in 7 patients (21.2%), 9 patients (27.3%) had horizontal or rotatory nystagmus, 17 patients (51.5%) had a vertical or oblique nystagmus, negative HST, or “central HINTS.” Discussion and Conclusions: The 9 patients had an evoked nystagmus pathognomonic for benign paroxysmal positional vertigo; in the remaining 17 cases, peripheral vestibular dysfunction could be excluded and central disorder may be suggested. Due to the prevalence of nystagmus of non-peripheral origin, a central nervous system involvement could not be excluded. However, due to the small sample size, a definite cause–effect relationship between vaccination and vertigo cannot be inferred. In light of expected third dose, large-scale and well-designed studies are needed to better define possible adverse reactions of the COVID-19 vaccine.